(untitled) (Research, Society and Development, 2021)
Objective: to describe the clinical profile of newborns under investigation for retinopathy of prematurity, admitted to a neonatal intensive care unit and intermediate care unit. Methodology: Quantitative research, transversal and documentary, through descriptive analysis. The data were extracted from the ROP Brasil group’s premature retinopathy exam form and from the electronic medical record, with the application of a questionnaire and analyzed in the SPSS software with the application of the chi-square test and calculation of the ’P-value’. Result: 111 forms were analyzed; (n = 99) of the mothers had prenatal care, (n = 59) had a caesarean delivery and (n = 17) had pre-eclampsia during pregnancy. Most of the RNP are female (n = 58) with gestational age less than 36 weeks (n = 83) and weight less than 1500g, Apgar showed between 7 and 10 in the 1st and 5th minute. (n = 109) of the RNP used O2 (n = 100) for more than 20 days (n = 54). (n = 57) did not present the disease, however (n = 29) they were in stage 2, (n = 13) stage 1, (n = 11) stage 3 and (n = 1) stage 4, treated with laser. (n = 52) were discharged after follow-up and (n = 8) required treatment with anti-VEGF. Conclusion: This study enabled an alert to health professionals about the importance of screening for ROP and the impact on premature infants. It is necessary to sensitize the team through in-service education, in order to achieve qualified assistance to newborns at risk.